The mercantile dilemma: formalisations and historical conclusions - Saccal, Alessandro (Journal of Mathematical Economics and Finance; Vol 8 No 1 (2022): JMEF, Volume VIII, issue 1(14), Summer 2022DO - 10.14505/jmef.v8.1(14).03, 2022)
The following contributions are hereby worked: one mathematically formalises Mundell’s Impossible trio and Rodrik’s Globalisation paradox, supplying the latter with a taxonomy in terms of the current account; by means of Kaldor’s price endogeneity in output, one proves that external real money market disparity and trade generate external output mismatches and lead to autarky unless offset, using topology and dynamical systems; one characterises transfers and federalism and shows that all unitary states are federal polities and can merge into confederations; one demonstrates that the said external output mismatches can be only eluded via autarky or neutral- isation, irrespective of federalism; one discerns (i) artificial currency areas guaranteeing inter-regional external output growth equality and (ii) modern protectionism as two Nash equilibria, to wit, the mercantile dilemma, especially rationalising the nexus between the Gold standard, the Industrial revolution and the Great divergence therethrough.